Can health status questionnaires be used as a measure of physical activity in COPD patients?. Issue 5 (25th February 2016) - Demeyer, Heleen; Dueñas-Espín, Ivan; De Jongh, Corina; Louvaris, Zafeiris; Hornikx, Miek; Gimeno-Santos, Elena; Loeckx, Matthias; Vogiatzis, Ioannis; Janssens, Wim; Hopkinson, Nicholas S.; Rabinovich, Roberto A.; Karlsson, Niklas; et al.
Acting to address the amount of physical activity of patients with chronic obstructive pulmonary disease (COPD) is recommended as part of the Global Initiative for Chronic Obstructive Lung Disease (GOLD) recommendations [1]. A level lower than approximately 5000 steps for day (sedentary lifestyle index) is associated with significantly increased health risks [2, 3]. Actively screening to identify patients below this threshold could be an important step towards targeting interventions to increase physical activity. Potential screening tools include activity monitors (objective assessment) or self-reported questionnaires (subjective assessment) to measure the amount of physical activity [4]. The latter method, which is feasible in clinical practice, may not result in an accurate representation in an individual patient, as questionnaire responses tend to misclassify physical activity [5]. Although more accurate and widely used in research, activity monitoring is not yet commonly included in patients' routine assessment. Several health status questionnaires in routine clinical use contain a domain or dimension related to physical activity [6]. In the analytical framework of Leidy [7], functional performance has been defined as the physical, psychological, social, occupational and spiritual activities that people actually do in the normal course of their lives to meet basic needs, fulfil usual roles, and maintain their health and wellbeing. A review by Kocks et al . [8] proposed that these questionnaires could be used in the measurement of functional performance (defined as "what a patient is actually doing") and that this would be a more practical alternative to physical activity monitoring. Whether this approach is sufficiently valid as a representation of physical activity levels in clinical practice remains to be established. Health status questionnaires provide only limited insight into the physical activity of patients with COPD http://ow.ly/X7oUb